(untitled) - Davis, Stephen R. (Hoboken, N.J., 2010)
Learn to think like a programmer and understand how C++ works, create programs and get bugs out of your code, [and] master basic development concepts and techniques in C++
Keywords: C++ (Computer program language),C++ (Ngôn ngữ lập trình máy tính)